Paleotopographic influences of the Cretaceous/Tertiary angular unconformity on uranium mineralization in the Shirley Basin, Wyoming - James H. Covington; Patrick Kennelly (Journal of Maps, 2018)
The Shirley Basin is a small asymmetric synclinal structure located in northern Carbon County, Wyoming approximately 65 km (40 miles) south of Casper, Wyoming, USA. The basin formed during the Laramide orogeny of the Late Cretaceous to Early Tertiary (78–49 Ma) and contains economically significant uranium deposits. The underlying Cretaceous units form an angular unconformity with the overlying Tertiary units that represents a paleotopographic erosional surface characterized by stream channels and overbank deposits of interbedded sand and clay with some organic detritus. Furthermore, the Cretaceous shales function as the lower confining unit/aquitard for in-situ recovery (ISR) uranium mining, and the overlying Tertiary sandstones host the uranium mineralization. This study maps the K/T boundary in greater detail than previous studies and identifies paleotopographic features that influence sedimentary environments and structures that favor uranium mineralization. Using a larger study region and thousands of historical wells and associated electric logs not available to previous studies, this research identifies unit boundaries and enters them into Golden Software’s Surfer and Esri’s ArcGIS to construct a detailed structure contour map on the K/T surface. The map delineates paleotopography such as hills and river channels, with the latter showing a strong spatial association with uranium mineralization. Geologists can use these maps to identify thicker host sands and fluvial features which enhance uranium mineralization. Mining companies can reduce operational and exploration costs by drilling in these more favorable areas to efficiently delineate the ore body geometry and develop more accurate mine unit designs that will maximize uranium recovery.